The beginnings of a new aesthetic. Reflections on one film dramaturgy - Musil, Robert (Iluminace, 1994)
A classic essay by Austrian writer Robert Musil on film as an art form, first published in Der Neue Merkur magazine in 1925.
Keywords: film aesthetics